Religious heterogeneity and fiscal policy: Evidence from German reunification - Ronny Freier; Benny Geys; Joshua Holm (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Theoretical work based on social identity theory and in-group favoritism predicts that increased population diversity (e.g., due to immigration) reduces support for redistributive public policies. In this article, we add to the empirical literature testing this prediction in three ways. First, rather than ethno-linguistic or racial heterogeneity, we analyze religious diversity, which in many countries is an increasingly important source of diversity. Second, to account for the potential endogeneity of heterogeneity, we analyze an exogenous shock in diversity due to the German reunification. Finally, we assess shifts in local individuals' social identification after immigration took place, which, while untested in previous contributions, is a critical theoretical mechanism. Our results - using tax and spending decisions of 2031 Bavarian municipalities over the 1983-2005 period - indicate that Catholic municipalities in particular significantly reduced their level of taxes and spending in response to non-Catholic immigration. These effects arise only after the first post-reunification local elections, suggesting a critical mediating role of the democratic process.
Keywords: H10; H11; H77; 330; local identity; fiscal policy; redistribution; German reunification; diff-in-diff estimation